PENGARUH MEDIA LATIHAN TERHADAP PENINGKATAN TEKNIK DASAR TENDANGAN SABIT PADA CABANG OLAHRAGA PENCAK SILAT - Dimas Abdulrahman; Edi Purnomo; Rahmat Putra Perdana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstrakThis study aims to see the effect of training media on the results of improving the basictechnique of the sickle kick. This study uses experimental research methods. The population in this study is the fighter of the Persaudaraan Setia Hati Terate Branch Tebas, totaling 21 people. Sampling in this study used a purposive sampling technique, namely fighters with criteria aged 15-19 years and male. Data analysis was performed using t-test. The result of data analysis is that t-test = 6.09 is greater than the value of t-table = 1.73961, thus, there is a significant effect of training media on improving the basic technique of the sickle kick. The percentage of influence obtained is 45.63%. This isalso based on the results of the first test or pretest which shows a result of 19.04 which is smaller than the result of a test that has been given treatment or posttest which is 29.78. This proves that the results of the basic sickle kick technique exercise using trainingmedia have increased. And therefore the application of media in training can improve and enhance the perfection of the basic motion of the sickle kick in the sport of pencak silat.Keywords :Pencaksilat,sickle kick, training media